Longitudinal study of preadolescent sport self-concept and performance: reciprocal effects and causal ordering. - Marsh, H; Gerlach, E; Trautwein, U; Lüdtke, O; Brettschneider, W (2007)
Do preadolescent sport self-concepts influence subsequent sport performance? Longitudinal data (Grades 3, 4, and 6) for young boys and girls (N= 1,135; mean age = 9.67) were used to test reciprocal effects model (REM) predictions that sport self-concept is both a cause and a consequence of sport accomplishments. Controlling prior sport performance (performance-based measures and teacher assessments), prior sport self-concept had positive effects on subsequent sport performance in both Grade 4 and Grade 6 and for both boys and girls. Coupled with previous REM studies of adolescents in the academic domain, this first test for preadolescents in the sport domain supports the generalizability of REM predictions over gender, self-concept domain, preadolescent ages, and the transition from primary to secondary school.